The Effect of 2011 Revised Code of Corporate Governance on Pricing Behaviour of Nigerian Auditors - Salau O. Abdulmalik; Ayoib Che Ahmad (European Financial and Accounting Journal, 2015)
The paper examines the extent which risk management committee and corporate governance committee predict audit fees in Nigeria. We employed random panel data (unbalance) regression analysis to establish whether risk management committee and corporate governance committee affect audit fees. We obtained the data used for this study from the annual reports of public listed companies on the Nigerian Stock Exchange for the periods 2008-2013. Our results indicate a positive relationship between establishment of risk management committee and audit fees while the establishment of corporate governance committee has an insignificant relationship with audit fees. The findings provide evidence to inform policy makers and corporation in Nigeria on how their governance structure affects audit fees. Firms with a strong governance structure have the incentive to improve the quality of their financial report. Therefore, such firms will increase the scope of auditor's work. This result has implication for policy makers because it suggests that corporate governance mechanisms are important in ensuring a quality audit. The paper contributes to literature on audit pricing in the context of the Nigerian audit market that is currently under-researched. The study provides additional theoretical insights by investigating the impact of risk management committee and corporate governance committee on audit fees, which to the best of the researcher's knowledge, have not been tested in the audit fees model.
Keywords: M42; 650; Audit fees; Corporate governance committee; Risk management committee